2010
DOI: 10.1007/s10555-010-9238-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cancer cell invasion and metastasis by genistein

Abstract: Genistein is a small, biologically active flavonoid that is found in high amounts in soy. This important compound possesses a wide variety of biological activities, but it is best known for its ability to inhibit cancer progression. In particular, genistein has emerged as an important inhibitor of cancer metastasis. Consumption of genistein in the diet has been linked to decreased rates of metastatic cancer in a number of population-based studies. Extensive investigations have been performed to determine the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(119 citation statements)
references
References 173 publications
(197 reference statements)
2
114
0
3
Order By: Relevance
“…We found that HOTAIR and miR-141 expression are inversely correlated in renal carcinoma cells. Genistein has potent biological activity, regulates several signaling pathways in cancer cells, and promotes cancer cell death (29,30,50,51), and we have found that genistein regulates miRNAs (33,(52)(53)(54). We also found that genistein decreases HOTAIR expression while stimulating miR-141 expression, showing an inverse effect.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…We found that HOTAIR and miR-141 expression are inversely correlated in renal carcinoma cells. Genistein has potent biological activity, regulates several signaling pathways in cancer cells, and promotes cancer cell death (29,30,50,51), and we have found that genistein regulates miRNAs (33,(52)(53)(54). We also found that genistein decreases HOTAIR expression while stimulating miR-141 expression, showing an inverse effect.…”
Section: Discussionmentioning
confidence: 54%
“…Genistein has been shown to induce apoptosis and cell cycle arrest and to inhibit cancer cell proliferation (29) and invasion (30 DU145 prostate cancer cells have a relatively higher expression level of HOTAIR and miR-141 compared with non-malignant RWPE-1 prostate cells (31). miR-141 has been reported to function as a tumor suppressor in DU145 cells (32).…”
Section: Inverse Expression Of Hotair and Mir-141 In Renalmentioning
confidence: 99%
“…Genistein is considered that inhibit cell proliferation through regulation of MAPK [28][29][30] , and inhibit phosphorylation of ERK and Akt [31][32][33] . The high concentration group (G100) showed suppress the cell proliferation after 3 days incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a decrease in NF-kB activity by genistein in prostate cancer cell lines suggesting an indirect effect of genistein on tumor proliferation [8].…”
Section: Soy Phytoestrogens On Dna Methylation In Prostate Cancermentioning
confidence: 94%